Social inequalities in fruit and vegetable consumption by household characteristics in Argentina - Matías Salvador Ballesteros; María Elisa Zapata; Betina Freidin; Camila Tamburini; Alicia Rovirosa (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
Low consumption of fruits and vegetables contributes to an increased burden of non-communicable diseases. In order to analyze the impact of different factors on fresh fruit and vegetable consumption, an observational, correlational, and cross-sectional study was conducted using data collected in the 2017-2018 National Household Expenditure Survey. We calculated apparent intake of fresh fruits and vegetables in net grams. Descriptive bivariate and multivariate analyses were conducted using multiple linear regression. Apparent intake of fresh fruits and vegetables was well below the recommended level; the lowest consumption was observed in households with lower incomes, with lower educational levels, without elderly members, with children under age 14, with a male head of household, and those residing in the Argentine Northeast region. Identifying social inequalities in food consumption contributes to the development of policies aimed at promoting food and nutrition security.